Aeromonas sobria Serine Protease Degrades Several Protein Components of Tight Junctions and Assists Bacterial Translocation Across the T84 Monolayer - Ueda, Mitsunobu; Kobayashi, Hidetomo; Seike, Soshi; Takahashi, Eizo; Okamoto, Keinosuke; Yamanaka, Hiroyasu (Frontiers in Cellular and Infection Microbiology, 2022)
Aeromonas sobria is a Gram-negative pathogen that causes food-borne illness. In immunocompromised patients and the elderly, A. sobria opportunistically leads to severe extraintestinal diseases including sepsis, peritonitis, and meningitis. If A. sobria that infects the intestinal tract causes such an extraintestinal infection, the pathogen must pass through the intestinal epithelial barrier. In our earlier study using intestinal cultured cells (T84 cells), we observed that an A. sobria strain with higher A. sobria serine protease (ASP) production caused a marked level of bacterial translocation across the T84 intestinal epithelial monolayer. Herein, we investigated the effect of ASP on tight junctions (TJs) in T84 cells. We observed that ASP acts on TJs and causes the destruction of ZO-1, ZO-2, ZO-3, and claudin-7 (i.e., some of the protein components constituting TJs), especially in the strains with high ASP productivity. Based on the present results together with those of our earlier study, we propose that ASP may cause a disruption of the barrier function of the intestinal epithelium as a whole due to the destruction of TJs (in addition to the destruction of adherens junctions) and that ASP may assist invasion of the pathogens from the intestinal epithelium into deep sites in the human body.